(untitled) (Agricultural Engineering, 2017)
In order to support the designing process and selection of subassemblies of an installation, specialist application programs are created. Selected applications were compared in the paper through their use for designing hypothetical solar collector systems for a single family house with a varied number of household members. With the use of particular applications, calculations for the same input assumptions were made. Results obtained with the use of a traditional calculation method were a reference point. Applications were compared on account of the type and amount of input parameters which may be introduced, type and number of determined values and their value. Based on the obtained results usefulness and scope of use of an application were assessed.